2020
DOI: 10.3390/ijerph17238985
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Isolation on the Preventive Behaviors for Non-Communicable Diseases in Community-Dwelling Older Adults in Japan

Abstract: This study aimed to examine the relationship between one’s physical status related to non-communicable diseases (NCDs) and social isolation, and to identify lifestyle behaviors for the prevention of NCDs associated with social isolation among community-dwelling older adults in Japan. A cross-sectional study was conducted to investigate lifestyle behaviors for NCD prevention associated with social isolation in Japanese adults aged 60 years and above in a community setting. Out of 57 participants, 17.5% were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…These findings indicate that individuals experiencing a lack of social involvement were less inclined towards adopting a healthy diet. This relationship may be partially explained by the mechanism where social networks and communal activities, particularly in cultures valuing group harmony like Japan, enhance motivation for healthy behaviours through mutual support and shared values [35,36]. These insights complement our findings by underscoring the importance of addressing social isolation and promoting communal dining experiences as part of dietary interventions, particularly in aging societies like Japan.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings indicate that individuals experiencing a lack of social involvement were less inclined towards adopting a healthy diet. This relationship may be partially explained by the mechanism where social networks and communal activities, particularly in cultures valuing group harmony like Japan, enhance motivation for healthy behaviours through mutual support and shared values [35,36]. These insights complement our findings by underscoring the importance of addressing social isolation and promoting communal dining experiences as part of dietary interventions, particularly in aging societies like Japan.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Sakurai's (2021) study, which explored the association between dining alone, weak social networks, and depression among older Japanese individuals residing alone, highlights the significant impact of social connections on food choices and mental health [20]. Yamaguchi et al (2020) also studied the older adults in Japan and found that a lack of social participation was inversely related to the frequency of vegetable and fruit consumption [35]. These findings indicate that individuals experiencing a lack of social involvement were less inclined towards adopting a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…This frequency could be affected by the location of the video camera; however, there could also be participants who did not experience joy from the recreational activity because they had become used to being alone and were struggling to connect with other participants [ 31 ]. As society becomes more diverse and various individuals become part of the same communities, recreational activities can be adjusted to the various needs of older people [ 32 , 33 , 34 ]. Social isolation is one of the significant challenges faced by rural communities [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that social networks could be related to health outcomes through several pathways, including their influence on health-related behavioural patterns such as smoking, alcohol use or medical help-seeking ( 10 , 11 ) . However, limited studies have investigated the relationship between social networks and dietary habits among older adults ( 12 , 13 ) .…”
mentioning
confidence: 99%